Legenda Bunga Genggong Sebagai Inspirasi Penciptaan Batik Kontemporer Bernuansa Kearifan Lokal Kabupaten Probolinggo - Wulandari, Sri; Ramadhan, Bayu Gilang; Prihantanto, Yudha (Proceedings of Annual Conference for Muslim Scholars, 2024)
Cultural products that are noble are very diverse in Indonesia. One of them is the art of batik. On a piece of batik, not only does it visualize the beauty of the motif, but it also contains a philosophy that is closely related to the lives of the community. Of course, each region has various batik motifs that are thick with the local nuances of the area. The genggong flower is a typical flower that grows abundantly in Karangbong Village, Pajarakan District, Probolinggo Regency, which is legendary. Currently, the existence of the genggong flower can no longer be found, but the story of the beauty of the flower is legendary. It has been passed down from generation to generation by the local community. The legend of the beauty of the genggong flower is immortalized as the name of an Islamic boarding school, namely the Zainul Hasan Genggong Islamic Boarding School. Through in-depth information to local community leaders, the genggong flower has a history for the people who live around the Islamic boarding school. This exciting thing then became an inspiring idea to create contemporary batik creations with the genggong flower motif as the central motif, which is reinforced with the character of the natural nuance motifs typical of Probolinggo Regency. The process of creating contemporary batik with nuances of local wisdom of Probolinggo Regency uses an artwork creation procedure consisting of three stages, namely exploration, design, and manifestation. The first stage is exploration, including tracing, excavation, data collection, and references regarding the source of ideas about genggong flowers in the Karangbong Village area. The second stage includes (1) design, namely exploring forms and techniques; (2) visualization of ideas, making selected sketches as a form of the prototype model. The third stage includes (1) manifestation, developing/refining selected sketches that will be used as designs in the batik creation process. This creation process produces contemporary batik as a form of effort to preserve batik and add to the richness of batik motifs in Probolinggo Regency